Perception of parenting and coping style as predictors of non-suicidal self-injuries in adolescents - Salazar Suarez, Olivia; Van Barneveld, Johannes Oudhof; Robles Estrada, Ericka; Rodríguez Aguilar, Brenda (Acta Universitaria, 2023)
The purpose of this study was to determine if the perception of parenting and coping style predict non-suicidal self-injuries in adolescents. A non-probabilistic sample of 495 participants (38.4% male and 61.6% female) aged between 11 and 18 years in the State of Mexico was employed. The statistical analysis showed a presence of self-injury in 23.2% of the participants, with a higher mean score for girls than for boys on the skin (1.57 vs. 1.36) and underneath it (1.40 vs. 1.20). Statistically significant correlations were obtained between self-injuries and perception of parenting and productive coping styles, related to others and unproductive coping styles. It is concluded that coping styles and the perception of parenting affect the frequency of self-injuring by the participants in this study, and that to understand self-injuries it is necessary to consider diverse individual and contextual factors.